2019
DOI: 10.3389/fpsyg.2019.02552
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Job Dissatisfaction, and Mental Health Outcomes Among Medical Students and Health Care Professionals at a Tertiary Care Hospital in Pakistan: Protocol for a Multi-Center Cross-Sectional Study

Abstract: Burnout, a state of vital exhaustion, has frequently been related to work-related stress and job dissatisfaction. Given the emotionally and physically challenging nature of their work, high rates of burnout have been reported among health care professionals. This may put them at a higher risk for of suffering from adverse mental health outcomes, including depression, anxiety and stress. In our study, we aim to assess the prevalence i of and associations among burnout and job dissatisfaction and adverse mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Thus, these reasons would raise the levels of their stress during the pandemic, especially for medical students with their extensive duties (Arora, 2015). Of note, mild, moderate, and high levels of stress and even burnout have been reported among medical students and healthcare professionals in other countries (Al Khalidi and Wazaify, 2013;Muzafar et al, 2015;Aamir et al, 2017;Alkot et al, 2017;Syed et al, 2019). In total, understanding of the distribution and reasons of high stress in students during the COVID-19 outbreak may be helpful to governments, schools, or health authorities.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, these reasons would raise the levels of their stress during the pandemic, especially for medical students with their extensive duties (Arora, 2015). Of note, mild, moderate, and high levels of stress and even burnout have been reported among medical students and healthcare professionals in other countries (Al Khalidi and Wazaify, 2013;Muzafar et al, 2015;Aamir et al, 2017;Alkot et al, 2017;Syed et al, 2019). In total, understanding of the distribution and reasons of high stress in students during the COVID-19 outbreak may be helpful to governments, schools, or health authorities.…”
Section: Discussionmentioning
confidence: 96%
“…The experience of learning burnout has been found to be pervasive among university students across cultures (Ling et al, 2014;Stoliker and Lafreniere, 2015;Vahabi et al, 2018;Zhang, 2019), with negative psychological and behavioral consequences such as depression, anxiety and stress (Koutsimani et al, 2019;Mufarrih et al, 2019); low self-concept and engagement in learning (Widlund et al, 2018); and low academic achievement (Fiorilli et al, 2017). In particular, several studies conducted with Chinese samples have indicated the alarming prevalence of learning burnout in the college student population.…”
Section: Introductionmentioning
confidence: 99%
“…We adjusted the analysis by the weighting factor of the complex sampling. Two models were evaluated based on the hypothesis that job satisfaction in uences burnout syndrome, which in uences depressive symptoms 37,47,54 . The rst model (model 1) evaluated the relationship between job satisfaction, burnout, and depressive symptoms.…”
Section: Structural Regression Modelmentioning
confidence: 99%